1987
DOI: 10.1200/jco.1987.5.10.1523
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy versus chemoimmunotherapy (CAF v CAFVP v CMF each +/- MER) for metastatic carcinoma of the breast: a CALGB study. Cancer and Leukemia Group B.

Abstract: Three combination chemotherapy regimens each with or without the methanol-extracted residue of bacillus Calmette-Guérin (BCG) (MER) were compared for efficacy. After stratification for disease-free interval and dominant sites of disease, patients were randomized to either CMF (cyclophosphamide [CYC], 100 mg/m2 orally, days 1 through 14; methotrexate [MTX], 40 mg intravenously [IV], days 1 and 8; 5-fluorouracil [5-FU], 500 mg/m2 IV, days 1 and 8), or CAF (CYC, 100 mg/m2 orally, days 1 through 14; doxorubicin [D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
3

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(23 citation statements)
references
References 0 publications
2
18
0
3
Order By: Relevance
“…The overall response rates and survival for both arms of this trial were similar to those reported in large series using both CMF and Adriamycin-containing regimens (Coates et al, 1987;Cummings et al, 1985;Hayes & Henderson, 1987;Macaulay & Smith, 1986;Smalley et al, 1983). Occasionally, better results have been reported, particularly with Adriamycincontaining regimens (Aisner et al, 1987), but these have not been confirmed by other studies. Comparisons of results between different trials are difficult because of potential variations in the selection criteria used for patient entry.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The overall response rates and survival for both arms of this trial were similar to those reported in large series using both CMF and Adriamycin-containing regimens (Coates et al, 1987;Cummings et al, 1985;Hayes & Henderson, 1987;Macaulay & Smith, 1986;Smalley et al, 1983). Occasionally, better results have been reported, particularly with Adriamycincontaining regimens (Aisner et al, 1987), but these have not been confirmed by other studies. Comparisons of results between different trials are difficult because of potential variations in the selection criteria used for patient entry.…”
Section: Discussionsupporting
confidence: 76%
“…It must be noted that the doses of our CMF combination were lower than those reported in some other studies (Cummings et al, 1985;Aisner et al, 1987;Coates et al, 1987), but not all: the dose rate was in fact slightly higher than the higher of two dose levels of CMF compared in a recent trial (Tannock et al, 1988). In addition treatment actually delivered is often less than treatment planned: in a classic adjuvant CMF trial only 17% of patients received the intended dose (Bonadonna et al, 1981).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The most commonly used doxorubicin-based combinations are AC (doxorubicin, cyclophosphamide), and FAC (5-fluorouracil, doxorubicin, cyclophosphamide) [8]. Several randomized clinical trials showed higher RR and improvements in disease-free survival for patients treated with FAC compared to CMF [9][10][11][12][13][14]. Other studies showed equivalence between these regimens.…”
Section: Anthracyclinesmentioning
confidence: 99%
“…1,2 Primary chemotherapy can also be used as a model for comparing the activity of different drugs or combinations. It has been reported that anthracycline containing regimens are superior to cyclophosphamide, methotrexate, 5-fluorouracil (CMF) in advanced disease in terms of response rates and, less consistently, survival, [3][4][5][6][7] furthermore, when given in the adjuvant setting, those regimens have also been shown to reduce the risk of recurrence and death. 8 However, to the best of our knowledge, there is no information in the literature concerning the relative merits of CMF versus anthracycline containing combinations as primary treatments.…”
mentioning
confidence: 99%